Pengaruh Disiplin Kerja Dan Motivasi Terhadap Produktivtas Kerja (Studi Kasus Proyek Kereta Cepat Jakarta-Bandung PT. Wijaya Karya (Persero) Tbk Section 2 Karawang) - Sekarini, Sari; Nadeak, Banuara; Martini, Nelly (Universitas Gorontalo, 2024)
This study aims to determine and analyze the effect of work discipline and motivation on the work productivity of employees of High Speed Railway Jakarta-Bandung Section 2 . This research is a type of explanatory research, with a quantitative approach. The analytical method used is multiple regression analysis. The sample used in this study used total sampling or used the entire population totaling 85. The results of this study indicate that part there is a significant influence between work discipline on employee work productivity, and work motivation has a significant effect on work productivity of High Speed Railway Jakarta-Bandung Section 2. While the simultaneous test results show that work discipline and work motivation affect the work productivity of employee of High Speed Railway Jakarta-Bandung Section 2.